Predicting Financial Distress in Islamic Banking: Evidence from Bank Muamalat Indonesia Using the Springate Model and Financial Ratios - Rafiqi, Iqbal; Nadhirah, Afifah; Mujibno, Mujibno; Abidin, Zainal; Faizah, Maftuhatul (Al-Amien Prenduan for Islamic Institute, 2025)
This study assesses the potential for financial distress in Bank Muamalat Indonesia the country’s pioneering Islamic bank by integrating financial ratio analysis with the Springate predictive model. Triggered by persistent fluctuations in profitability metrics, the study investigates whether key financial indicators. Return on Assets (ROA), Return on Equity (ROE), Operating Expenses to Operating Income (BOPO), and Financing to Deposit Ratio (FDR) significantly influence financial distress. Using a descriptive quantitative design and quarterly data from 2016 to 2022, multiple regression results indicate that none of the selected ratios exert a statistically significant effect (p > 0.05). However, the Springate model consistently produced S-scores above the distress threshold (0.862), indicating financial resilience throughout the study period. The findings suggest that while traditional performance ratios may lack predictive accuracy in this context, the Springate model provides a more reliable early-warning framework for assessing financial health. This study contributes to the literature on financial risk diagnostics in Islamic banking and offers practical implications for enhancing Shariah-compliant internal supervision systems.